THE TRAINING ON THE IMPLEMENTATION OF PSAK 71 (FINANCIAL INSTRUMENTS) FOR THE ASSOCIATION OF YOUNG ACCOUNTANTS IN THE BANTEN REGION - Benyamin Melatnebar; Eugenius Laluur (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agug, 2022)
Accounting as a process for recording, calculating, grouping, and classifying, processing and presenting transaction data. Accounting has many important aspects to discuss, there are even times every year every statement of financial accounting standards undergoes several changes. This Community Service activity aims to provide training on the application of PSAK 71 financial instruments for the Young Accountants Association of the Banten Region, especially students at various universities spread throughout the Banten area in order to understand the essence of PSAK 71 financial instruments, namely there are significant changes in classifying and measuring financial assets. How PSAK 71 makes an estimate for bad debts. The method used is teaching, tutorial and discussion methods. Presentation by explaining, namely participants were given material directly from the speaker about PSAK 71. Then also discussed PSAK 71 in terms of taxation and provided illustrative examples related to calculating allowance for impairment allowances using Expected Credit Loss (ECL). The results of this community service were marked by the enthusiasm and ability of the participants for the presentation of the theory presented, the participants were quite critical and asked many questions. Simulation practice to calculate the benefits of trade receivables and impairment of trade receivables. The results of this community service activity in the form of a webinar are expected to be useful for students of accounting study programs, especially at various universities in the Banten area.